An Electronic Program based on The Quality Matters ™ Rubric Standards (QM) and its Impact on Reading Achievement and Executive Functions among Students with Reading Disabilities and Attention Deficit and Hyperactivity Disorder - Alawamreh, Hamzah (Dirasat: Human and Social Sciences, 2022)
The present study aims at investigating the impact of an electronic reading program based on Quality Matters (QM) on reading achievement and executive functions among students with reading disabilities and attention Deficit and hyperactivity disorder. The population of the study included all third grade students reading disabilities and attention Deficit and hyperactivity disorder in Asir region. The sample of the study contained seven students who were purposively selected to participate in the experiment. The researcher has prepared a test to measure the students’ reading achievement and executive functions. The test was developed through reviewing the relevant literature of the topic being studied and consulting the experts in special education, psychology and educational measurement. The validity and reliability of the test were ensured as well. In addition, the researcher developed an electronic reading program for developing reading achievement and executive functions of students with reading disabilities and attention Deficit and hyperactivity disorder. The program was developed to fulfill the needs of the students at this particular age. The present study used the quasi-experimental design to examine the impact of the electronic program on reading achievement and executive functions. For the statistical purpose, Wilcoxon Test were utilized to answer the Study questions. The results of this study revealed that there was a statistically significant difference between the Pre and post measurement in reading achievement and executive functions; this difference was in favor of post measurement.